Bridges and parallels in 175 years of in Central Europe and Hungary in the history of kindergarten education - about a new book - Pálmai, Dóra; Uherkovich, Orsolya (Autonomy and Responsibility Journal of Educational Sciences, 2022)
In 2013, a volume of studies honouring the history of kindergarten education was published under the title Bridges and parallels edited by Rózsa Kurucz, the Illyés Gyula Faculty of the University of Pécs Szekszárd, 355 pages.